The mitochondrial genome of Cavia aperea. Issue 3 (2nd July 2020) - Wahedi, Azizia; Günther, Anja; Weyrich, Alexandra; Sondheimer, Neal
Abstract: Cavia aperea is a wild guinea pig found throughout South America. The previously published mitochondrial sequence for C. aperea was highly divergent from the C. porcellus sequence and contained stop codons within open reading frames. Here we resequenced the mitochondrial genomes of C. aperea and C. porcellus . Both sequences reflect gene organization typical for mammalian mitochondrial DNA. Our C. aperea mtDNA sequence shows that all of the open reading frames are intact, but confirms the strikingly low level of sequence identity (92.7%) with the closely related C. porcellus mtDNA.